2022
DOI: 10.1111/jocs.16315
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte to high‐density lipoprotein ratio at hospital admission predicts intrahospital mortality in patients with Stanford type‐A dissection

Abstract: Background Immune inflammatory mechanisms have crucial roles not only in the presence but also in the progression of aortic dissection (AD). Monocyte count to high‐density lipoprotein ratio (MHR) has recently emerged as an indicator of inflammation and oxidative stress. Thus, we aimed to examine the prognostic value of MHR in patients with AD. Methods A total of 204 consecutive patients with Stanford type‐A dissection who managed surgically were retrospectively enrolled in the present study. Recruited patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 33 publications
(63 reference statements)
1
11
0
Order By: Relevance
“…Lastly, the authors also discovered a significant correlation between admission CRP levels and MHR (r = .360, p < .002), further establishing MHR as a useful prognostic tool in AD. 6 This study is the first in the literature to investigate the prognostic relationship between MHR and TAAD, yet, MHR has been linked with myocardial infarction as well as bicuspid aortic valve degeneration, proving to be a useful tool in tackling the cardiovascular disease. [6][7][8] Xie et al 9 studied and confirmed MHR as a biomarker for in-hospital and long-term mortality in patients undergoing endovascular repair for acute type b AD.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Lastly, the authors also discovered a significant correlation between admission CRP levels and MHR (r = .360, p < .002), further establishing MHR as a useful prognostic tool in AD. 6 This study is the first in the literature to investigate the prognostic relationship between MHR and TAAD, yet, MHR has been linked with myocardial infarction as well as bicuspid aortic valve degeneration, proving to be a useful tool in tackling the cardiovascular disease. [6][7][8] Xie et al 9 studied and confirmed MHR as a biomarker for in-hospital and long-term mortality in patients undergoing endovascular repair for acute type b AD.…”
Section: Discussionmentioning
confidence: 95%
“…6 This study is the first in the literature to investigate the prognostic relationship between MHR and TAAD, yet, MHR has been linked with myocardial infarction as well as bicuspid aortic valve degeneration, proving to be a useful tool in tackling the cardiovascular disease. [6][7][8] Xie et al 9 studied and confirmed MHR as a biomarker for in-hospital and long-term mortality in patients undergoing endovascular repair for acute type b AD. Additionally, Du et al 10 looked at the diagnostic value of MHR in acute AD, providing further evidence in its favor.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations